2018
DOI: 10.1016/j.actamat.2018.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on micro-mechanical properties of polycrystalline Ti(C,N) and Zr(C,N) coatings

Abstract: Hard and wear resistant coatings are widely used as tribological layers to protect tools from wear, oxidation and corrosion. Characterizing the deformation behavior of coatings is essential for understanding wear mechanisms and to design multi-layered coatings that withstand severe working conditions. Micro-mechanical properties of Ti(C,N) and Zr(C,N) coatings deposited by chemical vapor deposition on a WC-Co cemented carbide substrate were examined by micro-compression testing using a nanoindenter equipped wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 74 publications
4
19
0
Order By: Relevance
“…In this study, Table 1 shows that there is nearly no solubility of Cl in Ti(C,N) (as the concentration is estimated about 200 ppm inside the grain) and the chlorine is rather segregated at the GBs up to 2.2 at.%. Additionally, Ti(C,N) has a finer grain size than Zr(C,N) [3] which is consistent with the role of chlorine in refinement of the microstructure [6,10,23]. Then, it is suggested that chlorine acts as an impurity, which is adsorbed on the crystal facets during film growth and segregates, yielding finally smaller grain sizes.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…In this study, Table 1 shows that there is nearly no solubility of Cl in Ti(C,N) (as the concentration is estimated about 200 ppm inside the grain) and the chlorine is rather segregated at the GBs up to 2.2 at.%. Additionally, Ti(C,N) has a finer grain size than Zr(C,N) [3] which is consistent with the role of chlorine in refinement of the microstructure [6,10,23]. Then, it is suggested that chlorine acts as an impurity, which is adsorbed on the crystal facets during film growth and segregates, yielding finally smaller grain sizes.…”
supporting
confidence: 68%
“…Regarding mechanical properties, segregation at the interfaces might reduce or enhance cohesion and bonding strength at GBs [2]. Within this context, the present study is a sequel to a recently published work [3], in which micromechanical properties of MT-CVD Ti(C,N) and Zr(C,N) coatings were studied by means of micropillar compression. A relevant finding of such work was that the brittle behavior of Ti(C,N) is dominated by low cohesive strength along the grain boundaries and pure columnar crack propagation, while Zr(C,N) coatings attested of a better cohesive strength and inter/transgranular failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2. Also, the deformation and micromechanical response of Ti(C,N) and Zr(C,N) micro pillars have been shown to be linear elastic with a high yield strength of 14 GPa [48]. Therefore, Hook's law should be sufficient to study the response of the nitrite systems.…”
Section: Elastic Stiffness Of Binary Phasesmentioning
confidence: 99%
“…Zirconium carbonitride (Zr(C,N)) is an alternative coating material to Ti(C,N), which presents excellent characteristics such as high hardness, elevated melting temperature and comparatively high electrical and thermal conductivities (IVASHENKO et al 2009, EL AZHARI et al, 2018.…”
Section: )mentioning
confidence: 99%